2013
DOI: 10.2105/ajph.2012.300969
|View full text |Cite
|
Sign up to set email alerts
|

Immigrant Generation and Diabetes Risk Among Mexican Americans: The Sacramento Area Latino Study on Aging

Abstract: Objectives We examined whether acculturation and immigrant generation, a marker for assimilation, are associated with diabetes risk in an aging Mexican-origin population. Methods We analyzed data on 1789 adults aged 60 to 101 years from the Sacramento Area Latino Study on Aging. We ascertained type 2 diabetes on the basis of diabetic medication use, self-report of physician diagnosis, or a fasting glucose of 126 milligrams/deciliter or greater. Logistic regression modeled prevalent diabetes. Results Adjust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 77 publications
2
35
0
Order By: Relevance
“…18,63 In this regard, our study lends support to the notion of “unhealthy assimilation. 15 Relating our findings to global changes in lifestyles and patterns in obesity and diabetes, may help elucidate some of the causal pathways implicated in this process of unhealthy assimilation.…”
Section: Discussionsupporting
confidence: 79%
“…18,63 In this regard, our study lends support to the notion of “unhealthy assimilation. 15 Relating our findings to global changes in lifestyles and patterns in obesity and diabetes, may help elucidate some of the causal pathways implicated in this process of unhealthy assimilation.…”
Section: Discussionsupporting
confidence: 79%
“…Explanations for this difference include the possible effect of heritage cultural influences on body image, food choices and physical activity [34]. Alternatively, measurement and definition of acculturation may be the reason since in a longitudinal study of older Mexican immigrants in the United States, immigrant generation (having foreign-born parents) but not length of residence was associated with diabetes [35]. That said, in our study we found a significant association between acculturation (measured by length of residence) and diabetes in migrant women.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were classified as: first generation Mexican-origin immigrant if they were foreign-born; second generation if they were US-born with at least one foreign-born parent; and third generation or higher if the participant and their parents were US-born. Second and third generation immigrants have been shown to have disparate risk of disease and exposure to social mobility; therefore, categorized separately (Afable-Munsuz et al, 2013; Haan et al, 2011). First generation Mexican-origin immigrants were further classified according to their duration of residence in the US: <15 years and ≥15 years (Creighton et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…However, this health advantage appears to diminish in offspring born in later generations and with longer US residence, despite improvements in protective health factors, including health insurance coverage and health care utilization. (Afable-Munsuz et al, 2013; Isasi et al, 2015; Kershaw et al, 2016a; Lara et al, 2005; Le-Scherban et al, 2016). For example, a recent study of immigrant generation and type 2 diabetes risk showed greater risk of diabetes among second and third generation Mexican-origin immigrants (highest among 3 rd generation immigrants) than first generation Mexican-origin immigrants, independent of sociodemographic factors including medical insurance (Afable-Munsuz et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation